Biological Mechanisms of Cancer-Induced Depression - Young, Kimberly; Singh, Gurmit (Frontiers in Psychiatry, 2018)
Patients with cancer are more likely to develop depression than the general population, which negatively impacts their quality of life and prognosis. In order to identify effective antidepressants catered towards cancer patients, the biology of depression in the context of cancer must be well-understood. Many theories have emerged postulating the mechanisms underlying the development of depressive disorder. Here, we review the role inflammation, a hyperactive hypothalamic-pituitary-adrenal (HPA) axis, and glutamate excitotoxicity may play in cancer-induced depression. Hopefully, novel therapeutics targeting these dysregulated pathways may be potent in ameliorating depressive symptoms in the cancer population.